'Plants out of place': The 'noxious weeds' eradication campaign in colonial south India. (July 2016) - Nongbri, Natasha
The spread of transferred plants such as the prickly pear and lantana, labelled 'noxious weeds' in late nineteenth- and early twentieth-century south India, and the exploration of viable means for their extirpation gave rise to a complex colonial discourse. Such plants not only seriously impeded agricultural and plantation interests but also threatened colonial commercial concerns. The eradication discourse consisted of various shades of opinion highlighting the ambivalences and contradictions within the eradication agenda. The increasing use of the legal domain as a regime of control by the colonial state was directed at legitimising the use of coercion for the destruction of undesirable plants. Notably, the use of legal coercion proved ineffective in the face of escalating costs of implementation and lack of local support. Local voices appealing against the enactment of eradication programmes were also attempts at opposing the colonial state's efforts at instituting a regime of control. The colonial state's eradication discourse and campaign against lantana in south India provide valuable insights into the then prevailing perceptions and attitudes towards exotics and invasives.